Ion source and Model 203-GGB Magnetic Electron Multiplier - Bendix Corporation (1959)
General view of an ion source and Model 203-GGB Magnetic Electron Multiplier designed for use with the Bendix Corporation Time-of-Flight Mass Spectrometer. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis, while the magnetic electron multiplier is used to detect and amplify ion bunches or peaks. According to notations accompanying the photograph, the Model 203-GGB Multiplier was part of the Rocket-borne and Satellite series.
Keywords: Photoelectric multipliers; Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers